Impact of Autumn-Winter Tibetan Plateau Snow Cover Anomalies on the East Asian Winter Monsoon and Its Interdecadal Change - Chen, Zhang; Wu, Renguang; Wang, Zhibiao (Frontiers in Earth Science, 2021)
The present study investigates the impacts of autumn-winter Tibetan Plateau (TP) snow cover anomalies on the interannual variability of the East Asian winter monsoon (EAWM). It is found that the northern component of EAWM is significantly associated with October-November-December-January (ONDJ) snow cover anomalies over the eastern TP, whereas the TP snow cover changes have little impact on the southern component of EAWM. However, the relationship of the northern component of EAWM to ONDJ TP snow cover experienced an obvious change in the mid-1990s. During 1979–1998, due to the high persistence of TP snow anomalies from autumn to winter, extensive ONDJ TP snow cover anomalies have a prominent influence on atmospheric circulation over Asia and the North Pacific, with more TP snow cover followed by an enhanced Siberian high and a deepened Aleutian low in winter, resulting in stronger EAWM. During 1999–2016, TP snow cover anomalies have a weak persistence. The atmospheric circulation anomalies display a different distribution. As such, there is a weak connection between the northern component of EAWM and the TP snow cover anomalies during this period.